Computational studies of the mechanisms of chemical reactions involved in mechanism-based inactivation of cytochrome P450 enzymes - Chuanprasit, Pratanphorn (2017)
The cytochrome P450 enzymes (P450s) play crucial roles in xenobiotic metabolism, especially drug metabolism. Even though metabolism is fundamentally an essential process, metabolic products could also lead to adverse effects. For example, in mechanism-based inactivation (MBI), a reactive metabolite acts as an inhibitor of a P450 and thereby reduces or eliminates the enzymatic activity. Such inhibition can have great influence on the metabolic profiles of drugs. An in-depth understanding of MBI of P450s will provide clues as to how to prevent this unwanted consequence during a therapeutic period. The complex mechanisms of the reactions ofP450s are hard to probe experimentally. Computational studies, based on small models or realistic models, are indispensable for gaining valuable insight into the enzymatic reactions. Through this thesis, computational methods, such as density functional theory (OFT), quantum mechanics (QM), and hybrid quantum mechanics/molecular mechanics (QM/MM) calculations are applied to some reactions of P450s pertaining to MBI. Through computational studies, valuable insights into MBI processes have been derived, which I believe is an important first step for the design of drugs free from MBI.